34.4: Invited Paper: Combinatorial Design of OLED‐Emitting Materials. Issue 1 (June 2015) - Aspuru‐Guzik, Alán; Adams, Ryan; Baldo, Marc; Aguilera‐Iparraguirre, Jorge; Gómez‐Bombarelli, Rafael
Abstract : We report the first results from a combinatorial design effort focused on new OLED emitters that exploit thermally‐activated delayed fluorescence. Using quantum chemistry and machine learning techniques to prune a pool of over 400, 000 combinations of donor and acceptor subgroups, we demonstrate new dyes that are state‐of‐the‐art, yet entirely computationally‐derived.